Health of young people as one of the elements of the state youth policy in Ukraine - Найдич, Марина Анатоліївна; Naidych, Maryna A. (Instytut Studiów Politycznych PAN, 2013)
The paper describes the healthcare system in Ukraine. The basic legal documents that relate directly to this issue are considered. The main health threats for Ukrainian youth are defined. Some of the social programs and projects related to healthy lifestyle of Ukrainian youth are examined.
Keywords: youth; health care system; HIV/AIDS; alcoholism; smoking; drug addiction